Akses Perbankan Syariah bagi Pengusaha Batik Muslim di Solo Raya - Usnan, Usnan; Pramesti, Wahyu; Yahya, Alvin (Jurnal Ilmiah Ekonomi Islam, 2024)
The aim of this research was to analyze how banking access for Muslim batik entrepreneurs in Solo Raya. This research was conducted in 2020 at 16 Muslim Batik entrepreneurs in Solo Raya, using qualitative methods, and data collection was carried out through interviews, observation and documentation techniques. The results of the study show that the access of Muslim batik entrepreneurs to Islamic Banking is still not optimal. This is due in part to several things, namely: (a) the distance of Islamic Banks to the location of the batik business, (b) prices are still higher at Islamic Banks, (c) the financing process at Islamic Banks is considered more difficult and more complicated, and (d) there is still a lack of education and outreach by Islamic Banks to the public, especially batik business actors in Solo Raya. Keywords : Banking Access, Muslim Batik Entrepreneurs.